The Role of Parents In Habituating Toilet Training to Train the Independence of Children - Novia Putri Wulandari; Nurkamelia Mukhtar; Siti Salina bt Samaun; Dewi Sri Suryanti; Yulia Novita; Zulfadhly Mukhtar; Issaura Dwi Selvi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was motivated by there are still children who are still not used to and show an independent attitude in the implementation of toilet training because children aged 1-3 years still do not show an independent attitude in habituating toilet training because many children use diapers, lack of parental care, lack of parental knowledge about toilet training. This study aims to determine the role of parents in toilet training habits to train the independence of children aged 1-3. This study uses a descriptive qualitative approach. The study population consisted of 101 children, with a sample of 11 children. Data collection techniques through interviews, observation and documentation. Miles and Huberman's model analysis techniques through data reduction, data presentation and drawing conclusions. The findings of this study: 2 out of 11 parents have not yet played a role, 7 out of 11 parents have started to play a role, and 2 out of 11 parents have played a role in toilet training habits. The results of the study 1) parents play a role in educating toilet training in the age range of 1-3 years, 2) parents play a role in raising children not to use diapers/diapers, not to wet the bed day/night, 3) parents play a guiding role through speech and action. The habit of toilet training is carried out through several stages, namely: teaching children to squat, wash themselves, urinate/ defecate in the toilet, go to the toilet by themselves, open/put on their own pants, and take off diapers/diapers day/night. Based on the results of the study it was concluded that the role of parents in toilet training to train the independence of children aged 1-3 years in Sumber Makmur Village, parents have started to act as educators, caregivers and mentors to train independence in children aged 1-3 years in Route 3 of Sumber Makmur Village Tapung District, Kampar Regency.Keywords: Role of Parents, Toilet Training, Independence